A Multimodal Discourse Analysis on the Cover of English Textbooks for Primary and Secondary Schools - Nur Cahyati (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2025)
This study explores the implied meanings embedded in the visual elements such as images, colors, and text, on the covers of English textbooks used in Primary and Secondary schools through the lens of Multimodal Discourse Analysis (MDA). It further examines how these visual components reflect and align with the content of the textbooks. Kress and van Leeuwen’s visual grammar framework is applied to analyze the representational, interactive, and compositional meanings, while Gee’s seven building tasks of language are used to interpret the linguistic features and how they construct identities, relationships, and ideologies. Data were collected through document analysis, following the procedures of Yildirim and Şimşek: identifying relevant textbooks, validating their authenticity, and interpreting both explicit and implicit meanings. The findings reveal that the visual designs on textbook covers are not merely decorative but serve a communicative function. For example, bright color palettes, smiling characters, and playful typography suggest a portrayal of English learning as engaging, child-friendly, and globally relevant. These visual strategies work together to construct a positive learner identity and subtly embed educational values. Overall, the study underscores the importance of textbook covers as multimodal texts that influence meaning-making in educational contexts. The use of visual semiotics provides valuable insights into how English language education is framed through design choices.